Equilibrium in the governance of cross-sectoral policies: how does it translate into practice? - Pernelle Smits; Johanne Préval; Jean-Louis Denis; Gerard Divay; Jacques Bourgeault; Nassera Touati (BMC, 2023)
Abstract Background There is growing interest from health researchers in the governance of Health in All Policies (HiAP). Furthermore, the COVID-19 pandemic has re-ignited managers' interest in HiAP governance and in health prevention activities that involve actors from outside health ministries. Since the dynamics of these multi-actor, multi-sectoral policies are complex, the use of systems theory is a promising avenue toward understanding and improving HiAP governance. We focus on the concept of equilibrium within systems theory, especially as it points to the need to strike a balance between actors that goes beyond synergies or mimicry-a balance that is essential to HiAP governance. Method We mobilized two sources of data to understand how the concept of equilibrium applies to HiAP governance. First, we reviewed the literature on existing frameworks for collaborative governance, both in general and for HiAP specifically, in order to extract equilibrium-related elements. Second, we conducted an in-depth case study over three years of an HiAP implemented in Quebec, Canada. Results In total, we identified 12 equilibrium-related elements relevant to HiAP governance and related to knowledge, actors, learning, mindsets, sustainability, principles, coordination, funding and roles. The equilibria were both operational and conceptual in nature. Conclusions We conclude that policy makers and policy implementers could benefit from mobilizing these 12 equilibrium-related elements to enhance HiAP governance. Evaluators of HiAP may also want to consider and integrate them into their governance assessments.